Wanita Pencari Nafkah dalam Pandangan Ulama Pedesaan - Ila Nurmila; Zaki Abdul Wahab; Miftah Farid (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2019)
Marriage is an important worship. Even marriage is a part of perfection in religion. This procession is a sacred thing. Everyone who does marriage must meet the pillars and marital requirements, which leads to the rights and obligations of both. The duty of a husband, as well as a wife varies according to his ability. The legal consequences of a legal marriage include: arising rights between husband and wife, husband becoming head of household and wife becoming housewife. Also arise the obligation of the husband to finance and educate the children and his wife, and seek a place to live with the obligation of the husband with regard to the necessities of life not only provide a living alone. the obligation of the husband also provides shelter, household expenses such as electricity, water and other needs, to the cost of care for the wife and children if they are sick.